SOCIAL MEDIA AND LOCAL WISDOM: ETHICAL COMMUNICATION MODEL FOR CONTENT CREATORS BUGIS-MAKASSAR - Hamson, Zulkarnain; Akbar, Muhammad; Aziz, Syamsuddin (International Journal of Multidisciplinary Research and Literature, 2025)
Social media has become a primary space for content creators to express ideas, share information, and build communities. However, digital communication practices often ignore local wisdom values amid globalization. This study aims to develop a communication ethics model for content creators with an approach to Bugis-Makassar's local wisdom values. Values ​​such as "sipakatau" (mutual respect), "sipakalebbi" (mutual glorification), and "sipakainge" (mutual reminder) are identified as relevant ethical foundations for creating dignified and inclusive communication on social media. With a qualitative approach, this study integrates literature analysis, in-depth interviews with local content creators, and observations of communication practices on social media. The study results indicate that applying Bugis-Makassar local wisdom in digital communication strengthens cultural identity and builds trust and solidarity in online communities. The proposed communication ethics model underlines the importance of balancing individual expression and social responsibility in creating meaningful and culturally valuable content. This research is anticipated to serve as a resource for content creators to integrate local values into digital communication practices, thereby contributing to the preservation of local culture in the context of globalization